Optimalisasi Pemanfaatan Platform Rumah Pendidikan dalam Mendukung Pengembangan Kompetensi Guru di SD Swasta Harapan 3 Deli Serdang - Cut Latifah; Mardiati; Novianti Harahap; Rizka Sri Windy Arini; Fadhlan AlMurtadho; Ida Rosianna; Alffredo Sihombing; Sezi Oktavia (LPPI UMN AL WASHLIYAH, 2025)
The digital transformation in education requires teachers to adapt and optimally utilize digital learning platforms. However, a common problem found in schools is the limited understanding and use of the Rumah Pendidikan platform as a medium for professional development, career management, and learning inspiration. This community service activity, conducted through the Field Work Course (Kuliah Kerja Lapangan/KKL), aimed to improve teachers’ understanding and skills in accessing and utilizing Rumah Pendidikan services effectively based on their professional needs. The activity employed a community education and training approach, including policy socialization, demonstrations of key features, and hands-on mentoring in using the platform. The results showed an improvement in teachers’ understanding of the functions and benefits of Rumah Pendidikan services, as reflected in their ability to independently access continuous learning, career and performance management, and learning inspiration features. Overall, this activity contributed positively to teachers’ readiness to integrate digital education platforms into daily teaching practices, supporting a more meaningful and sustainable educational transformation..